Analisis Dan Usulan Strategi Bauran Ritel Food Truck di Kota Bandung - Ignatius Bryan Abimanyu Wicaksono; Rakean Tajali Kahfi (Jurnal Akuntansi, 2019)
This study aims to determine the proposed strategic and retail mix for food trucks in the city of Bandung. The research method used in this study is explorative and descriptive research using interviews, surveys using questionnaires and observations. The sample in this study is a food truck that joins the Bandung Food Truck community, has a regular place, and still active in running a food truck retail business and 120 respondents who are consumers who visit and buy food truck products using purposive sampling technique. Data analysis is carried out qualitatively and quantitatively. The results showed that the food truck target market ranged in age from 15 to 25 years, knew the sources of information about food trucks through social media, and important factors in buying food trucks were products and respondents did not agree with the location of food trucks that were easily visible. The strategy carried out to promote through attractive social media adjusts to the times such as discounts, special menus and attractive booths to have a good impact and where food trucks become known and crowded. Keywords: Marketing Strategy, Retail Mix, Food Truck